Childhood Circumstances and Mid-life Functional Mobility - Mc Crory, Cathal (My University, 2016)
Objectives: We examine the cumulative long-term role of childhood health and socioeconomic status in affecting functional health at ages 50 to 59. Method: Data on 2,233 respondents to The Irish Longitudinal Study of Aging (TILDA) are used to examine functional health measured by the timed-up-and-go (TUG) test of lower-body mobility. We examine the association of father’s education, childhood rural residence, and childhood self-evaluated health with TUG and examine respondent’s education, adult health behaviors, measured health, and cognition as mediators of the association of childhood characteristics and TUG. Results: Father’s education, rural residence, childhood health, and education are associated with TUG times at ages 50 to 59. While health behaviors mediate most of the rural residence and education associations, the association with childhood self-evaluated health is direct. Discussion: Early life circumstances play substantial direct and indirect roles in molding functional level in late mid-life.
PUBLISHED
Keywords: disability, health behaviors, social factors, physical function, rural aging; Ageing; Ageing and the life-course